2023
DOI: 10.4152/pea.2023400603
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Treatment of Ni-Cu Alloy in a Deep Eutectic Solvent to Improve Electrocatalytic Activity in the Hydrogen Evolution Reaction

Abstract: The quality of the Souss-Massa Daraa (S-MD) aquifer is influenced by natural and anthropogenic contaminations. Indeed, geological formations are the main sources of mineralization in the aquifer, which compromises the potential irrigation, and threatens the sustainability of agricultural activities. In this context, hydrochemical and statistical studies were carried out on the major and secondary elements of water, based on different physico-chemical parameters, such as T °C, pH, EC (electric conductivity), NO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The experimental results demonstrated that the anodic modification of the Cu-Ni alloy surface in DESs induces notable alterations in its electrocatalytic behaviour towards the HER in an aqueous alkaline solution [4][5][6]. As is known, the exchange current density of an electrochemical reaction is a measure of electrocatalytic activity.…”
mentioning
confidence: 91%
See 3 more Smart Citations
“…The experimental results demonstrated that the anodic modification of the Cu-Ni alloy surface in DESs induces notable alterations in its electrocatalytic behaviour towards the HER in an aqueous alkaline solution [4][5][6]. As is known, the exchange current density of an electrochemical reaction is a measure of electrocatalytic activity.…”
mentioning
confidence: 91%
“…Two representatives of DESs were used: ethaline and reline (eutectic mixtures of choline chloride with ethylene glycol and urea, respectively). The methods for the ethaline and reline preparation have been described in numerous literature sources, including our previous publications [4][5][6][7][8][9][10].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to the surface composition and spatial arrangement exerting a remarkable influence on the hydrogen adsorption and desorption. Protsenko and coworkers demonstrated that the surface inhomogeneity of CuNi alloy will lead to unexpected HER behaviors and it is revealed that the structure and morphology are the reasons for improving the hydrogen evolution performance of the anodic-treated Ni-Cu alloy [ 33 , 34 ]. Despite the numerous studies performed regarding the beneficial effect of porous structure on HER performance, the reported data are, in some cases, inconsistent across different investigations.…”
Section: Introductionmentioning
confidence: 99%